Frame Complexity and the Financial Crisis: A Comparison of the United States, the United Kingdom, and Germany in the Period 2007–2012. (30th December 2014) - Kleinnijenhuis, Jan; Schultz, Friederike; Oegema, Dirk
Abstract Communicative complexity concerns the variety of issues and stakeholders (agenda complexity) and their associations (frame complexity) in the news. One issue may dominate news in crises (9/11, Katrina), but as soon as complexity recovers, uncertainty may decrease and the public mood may improve. The financial crisis in the United States, the United Kingdom, and Germany (2007–2012) offers an example. An automated content analysis was applied to over 160, 000 newspaper articles. Frame complexity decreased until the spotlight fell on the demise of Bear Stearns and Lehman Brothers (2008). The subsequent gradual recovery was only partly interrupted by the euro crisis. A Vector AutoRegression time series analysis shows that increasing frame complexity may indeed have fostered the recovery of financial markets and consumer confidence.